THE INFLUENCE OF GREEN MARKETING, SERVICE QUALITY AND BRAND IMAGE THROUGH PROMOTIONAL STRATEGIES AS INTERVENINNING VARIABLES ON PURCHASING DECISIONS IN STARBUCKS CONSUMERS COFFEE IN BATAM CITY - Desi Asmanianti; Indrayani; Mohamad Gita Indrawan; Chablullah Wibisono; Bambang Satriawan; Ngaliman (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
The aim of this research is to determine and analyze the influence of green marketing, service quality and brand image through promotional strategies as intervening variables on purchasing decisions for Starbucks Coffee consumers in Batam City. The method used was a questionnaire and distributed to 380 respondents. Statistical data analysis used SEM PLS. (Structural Equation Modeling Partial Least Square) and using path analysis to test the relationship pattern of the influence of the dependent variable on the independent, both direct influence and indirect influence with SMART PLS 3.0 software. The research results show. From the test results it was found that Green marketing has a significant positive influence on promotional strategies, service quality has a significant positive influence on promotional strategies, brand image has a significant positive influence on promotional strategies, promotional strategies as an intervening variable have a significant positive influence on purchasing decisions, green marketing has a positive and significant influence on purchasing decisions, Service quality has a positive and significant influence on purchasing decisions, Brand image has a significant positive influence on purchasing decisions, There is a significant influence between Green Marketing on purchasing decisions through promotional strategies as an intervening variable, There is a significant influence between service quality on purchasing decisions, through promotional strategies as an intervening variable, there is a significant influence between brand image on purchasing decisions.